Intellectual property and cultural property - Macmillian, Fiona (Elgar research reviews in law, 2022)
The number and variety of methodological and substantive challenges that face those working at the interface of intellectual and cultural property have generated a rich interdisciplinary literature. Responding to a myriad of questions that the juxtaposition of the concepts of intellectual property and cultural property provoke, this research review focuses on the importance of creativity and cultural production in social, political and economic terms. The text will be of value to anyone interested in this important frontier.